DIFFERENTIATION OF SOCIAL CAPITAL LEVEL IN RURAL CITIES OF THE WEST POMERANIAN VOIVODESHIP ACCORDING TO THE CRITERION FOR INCOME – RESEARCH RESULTS - Beata Będzik (Acta Scientiarum Polonorum. Oeconomia, 2018)
Evolution of societies means that factors that generate socio-economic development also evolve. Classic growth determinants are not enough to further improve the economic situation. The paper draws attention to the so-called soft factors, which are increasingly important in generating progress in highly developed countries, and focuses on one of them, i.e. social capital. It forms on the basis of trust, cooperation, participation, and these components have the strongest influence in the immediate environment. At the same time, the strength of their impact decreases with the increase of the radius of range. Therefore, it implies the selection of measurement tools which optics should be limited locally. Therefore, the aim of the article is to present the relationship between social capital and income at the local level, i.e. in rural communes of the West Pomeranian Voivodeship. This is important due to the search for categories that could contribute to creating and multiplying social capital.